The Correlation between Students’ Willingness to Communicate and Their Speaking Performance at the Tenth Grade of MAN 1 Pekanbaru - muhammad ichsan al -hafiz; rizky gushendra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The purpose of this research is to examine whether there is any significant correlation between willingness to communicate and speaking performance at the tenth-grade students of MAN 1 Pekanbaru. There were 244 students as samples by using the simple random sampling technique. This research approach was a quantitative method and the technique used in this research was a correlational technique. In collecting the data, the writer distributed the questionnaire to the respondents to determine the willingness to communicate, which consist of 55 item statements and used documentation of the students' speaking score made by English teachers at the school to determine the speaking performance. The writer used Spearman correlation through SPSS 26.0 to analyze the data. The result of this research showed that sig.r obtained value is 0.000 lower than alpha value (0.05). it means that null hypothesis (Ho) is rejected while alternative hypothesis (Ha) is accepted. In conclusion, there is a correlation between willingness to communicate and speaking performance at the tenth-grade students of MAN 1 Pekanbaru.